The Multi-Method Approach to Building the Model of Personnel Competences - O. M. Sharipova (Вестник Российского экономического университета имени Г. В. Плеханова, 2020)
Adequately plotted valid model of personnel competences can considerably increase the efficiency of enterprise functioning, promote the attainment of strategic objectives and optimize business -processes. The model of competences built in the system of personnel management gives an opportunity to use effectively such advantaged of the enterprise as human capital. The article demonstrates key approaches to the development of the competence model and analyzes their merits and drawbacks. The author puts forward the multi-method approach to designing the model of competences at the enterprise based on grouping of different methods of plotting the competence model and appraisal of personnel, shows advantages of using this mech anism, which can lead to max validity of the model. The mechanism consists of stage-by-stage algorithm of competence model development. The article provides recommendations for each of these stages. The universal nature of the approach allows us to plot th e competence model at enterprises of different fields of work, to use max number of personnel categories at the enterprise, which can provide the maximum validity f the model.